Study protocol for comparing the efficacy of left-open single-flap technique versus double-flap technique after proximal gastrectomy: A multicenter randomized controlled trial - Yang, Qin Chuan; Wang, Wei Dong; Mo, Zhen Chang; Yue, Chao; Zhou, Hai Kun; Gao, Rui Qi; Yu, Juan; Dong, Dan Hong; Liu, Jin Qiang; Wei, Jiang Peng; Yang, Xi Sheng; Ji, Gang; et al. (Frontiers in Oncology, 2022)
Background: Proximal gastrectomy has gradually gained more attention due to its superiority in retaining the function of part of the stomach. As a result of proximal gastrectomy, inevitably, the loss of the antireflux barrier and postoperative complications can severely affect the quality of life. Through the continuous improvement of digestive tract reconstruction after proximal gastrectomy, a variety of methods with antireflux functions have been developed. Recently, our center attempted the left-open single-flap technique and initiated a multicenter, prospective, randomized controlled trial for patients undergoing proximal gastrectomy to reduce the difficulty of surgical anastomosis and the incidence of perioperative complications compared with the double-flap technique. These findings will provide more evidence-based medical research for the development of clinical guidelines. Methods/design: This is a prospective, multicenter, randomized controlled clinical trial. We planned to recruit 250 patients who were eligible for proximal gastrectomy. After informed consent was obtained, patients were randomly assigned to the trial group (left-open single-flap technique) and the control group (double-flap technique) in a 1:1 allocation ratio. Discussion: Increasingly, clinical studies focus on the improvement of reconstruction modalities after proximal gastrectomy. Among these methods, the double-flap technique is a clinically effective method. The purpose of this study was to establish a prospective randomized controlled trial to compare the efficacy of the left-open single-flap technique versus the double-flap technique after proximal gastrectomy, aiming to provide more evidence-based medical studies for digestive tract reconstruction in proximal gastrectomy. Trial registration: This study was approved by the Chinese Ethics Committee of Registering Clinical Trials (ChiECRCT20210482) and registered on Clinical Trials.gov with the registration number NCT05418920.